ANALISIS KEMAMPUAN SISWA DALAM MENULIS PANTUN KELAS IV SD SE-GUGUS I KI HAJAR DEWANTARA KECAMATAN BUKIT RAYA PEKANBARU - Rasyidah Ratnaputri; Otang Kurniaman; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this study was conducted because of the problem that faced by the four grade of students elementary school. In writing, the students were still often mistakes especially in writing poem. Just a few of students who can write poem base on the correct criteria of writing poem. Some of the students had mistake on writing poem. The criteria in writing poem are the correct row in a verse, the total of syllable, verse, and the countain of poem. Most of students in elementary school can’t require that criteria. This research was writing test, which is the researcher asked the students write poem. The teacher give two themes, and the students freely to choose the theme. The themes are about advice and social. Based on the result of the research, from 99 students were analyze, 87 students can be categorized “very good” (87,88%), 6 students are “good”(6,06%), 6 are categorized “enough”, and there isn’t who get the criteria of “poor”in test. The mean score of students ability in writing poem is 94, and it can be categorized “very good”. This result shown that, the ability of the students at the four grade of elementary school as cluster Ki Hajar Dewantara Pekanbaru district is “very good”.Key Words: Writing ability, Poem